Heterotic Kerr-Schild Double Field Theory and its double Yang-Mills formulation - Eric Lescano; Sourav Roychowdhury (Journal of High Energy Physics, 2022)
Abstract We present a formulation of heterotic Double Field Theory (DFT), where the fundamental fields are in O(D, D) representations. The theory is obtained splitting an O(D, D + K ) duality invariant DFT. This procedure produces a Green-Schwarz mechanism for the generalized metric, and a fundamental gauge field which transforms as a gauge connection only to leading order. After parametrization, the former induces a non-covariant transformation on the metric tensor, which can be removed considering field redefinitions, and an ordinary Green-Schwarz mechanism on the b-field. Within this framework we explore perturbative properties of heterotic DFT. We use a relaxed version of the generalized Kerr-Schild ansatz (GKSA), where the generalized background metric is perturbed up to quadratic order considering a single null vector and the gauge field is linearly perturbed before parametrization. Finally we compare the dynamics of the gauge field and the generalized metric in order to inspect the behavior of the classical double copy correspondence at the DFT level.